Social-Costs Perspective Impacts of Cybercrime in World-Economy, Country-Wise: Policy-Guidance under Piecemeal Approach - Rahman, Dr. Akim M.; Islam, Saadi (Information Management and Business Review, 2021)
Today’s technology-driven human-society(s) country-wise are counted more than ever before where UAE-society is no exception. Tech-users here compete for comparative time-saving options for marginalizing operating costs. It has resulted in huge data usages, a high number of users & devices, which has attracted criminals for taking advantage, which is called cybercrime. Addressing cybercrime, the UAE, like many countries, is not out of control by-laws. However, laws like cybercrime for its society are not always for absolutely eliminating the crime. Thus, besides cybercrime law in place, UAE needs a piecemeal approach in practice where one department may vary from approaches of other-department. With awareness about risky online behaviors & options, tech-users as defenders are needed to invest their efforts. This study has laid out the foundation of the proposal, Akim’s Model-2021, using the Theory of Consumer Choice & Behaviors and Welfare Analysis. Tech-user’s actual utility-received is the sum of utility-received from awareness & own-effort and utility-received from cybercrime-law. Any changes to services received from joint efforts may risk tech-user, to be a victim. Welfare analysis shows tech user’s actions - awareness & own-effort, besides cybercrime-law can create, Net Social-gain, which largely depends on tech user’s actions. Tech-user’s economic surplus is greater than government expenses for implementation of cybercrime law in UAE. Net-loss to the UAE is the sum of deadweight loss and net-loss to tech producers for underutilized resources.